PTU-190 Small Bowel Capsule Endoscopy in Patients with Unexplained Anaemia/Gastrointestinal Bleeding and Chronic Kidney Disease. (4th June 2013) - Docherty, E; Koulaouzidis, A; Douglas, S; Plevris, J N
Abstract : Introduction: The use of small-bowel capsule endoscopy (SBCE) has revolutionised investigating the small-bowel. However, there are only few reports 1, 2 on the Diagnostic Yield (DY) of SBCE in patients (pts) with chronic kidney disease (CKD) and unexplained anaemia and/or obscure gastrointestinal bleeding (OGIB). Methods: Retrospective study; our SBCE database was searched (March 2005 to August 2012) for pts with estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m2. Subsequently, electronic case notes of pts with low eGFR who underwent SBCE for anaemia and/or OGIB were retrieved and abstracted. A mean eGFR value -for up to 5 years prior to SBCE- was calculated for each case. Severity of CKD was defined according to Renal Association recommendations as: stage 3 (eGFR: 30–59); stage 4 (eGFR: 15–29); and stage 5 (eGFR < 15 or on dialysis). Numerical values were expressed as mean ± SD or median (range). Results: In the aforementioned period, 69 pts with eGFR < 60 were referred for SBCE. 65/69 (92.8%) had CKD stage 3 (eGFR 49 ± 7.9) and 4/69 (7.2%) stage 4 ( n = 3) or 5 ( n = 1). 51/65 (78.5%) of stage 3 CKD pts were referred for SBCE due to unexplained iron deficiency anaemia and/or OGIB [43 (66.1%) & 8 (12.3%), respectively]. 25/51 (49%) had normal SBCE, while 17/51 (33.3%) had angioectasias; other findings were active bleeding ( n = 2), non-specific fold oedema ( n = 2), ileal erosions ( n = 1), adenocarcinoma ( n = 1) and inconclusive/videos not available ( n = 3). All pts ( n = 4) with CKD 4 or 5 were referred due to unexplained anaemia. 3/4 (75%) had angioectasias and 1 normal SBCE. Faecal calprotectin (FC) was measured in 12 pts with CKD stage 3 and unexplained anaemia prior to SBCE; No sinister pathology or significant small-bowel inflammation was found in this subgroup. Conclusion: SBCE has limited DY in CKD pts referred for investigation of unexplained anaemia. The most common finding is angioectasias, while sinister small-bowel pathology is rare. Furthermore, FC measurement prior to SBCE -in this cohort of pts- is not associated with increased of DY. Disclosure of Interest: None Declared. References: Karagiannis S et al . Wireless capsule endoscopy in the investigation of patients with chronic renal failure and obscure gastrointestinal bleeding (preliminary data). World J Gastroenterol 2006; 12:5182–5. Ohmori T et al . Abnormalities of the small intestine detected by capsule endoscopy in hemodialysis patients. Intern Med 2012; 51:1455–60.